2010
DOI: 10.1007/s11244-010-9486-8
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Cr–Ti Binary Oxide Anchored Mesoporous Silica by CVD Method and Their Photocatalytic Activities

Abstract: Cr-Ti binary oxide anchored mesoporous silica (Cr-Ti/MCM-41) was prepared by stepwise CVD treatments of MCM-41 with TiCl 4 and CrO 2 Cl 2 . Cr-Ti/MCM-41 exhibited higher efficiency for the photocatalytic polymerization of ethylene as well as the oxidation of CO into CO 2 than those on single component Cr 6? -oxide anchored MCM-41 under UV and visible light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Since it is widely accepted that the active sites of redox catalytic processes are tetrahedral transition metal ions [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], we have looked for the method that allow removing the Al atoms from the zeolite and then incorporating the transition metal ions in its framework to obtain isolated metal single-site catalyst. However, there is the problem to obtain single-site catalyst with identical and well separated active sites related to two types of complexity, one arising from the oxide support and the other from the precursor aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…Since it is widely accepted that the active sites of redox catalytic processes are tetrahedral transition metal ions [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], we have looked for the method that allow removing the Al atoms from the zeolite and then incorporating the transition metal ions in its framework to obtain isolated metal single-site catalyst. However, there is the problem to obtain single-site catalyst with identical and well separated active sites related to two types of complexity, one arising from the oxide support and the other from the precursor aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the present work is to improve the rate of CHA oxidation while maintaining high oxidation selectivity. Some literature reports that Ti species, when incorporated into Cr-containing materials, enhances the photocatalytic activity under visible-light irradiation, even though Ti species does not absorb visible light. Rodrigues et al reported that MCM-48 containing Cr and nanosized TiO 2 , prepared by a hydrolysis of TEOS, Cr(NO 3 ) 3 , and titanium tetraisopropoxide (TTIP), shows higher activity for degradation of acetaldehyde in the gas phase than MCM-48 containing Cr alone. Shen et al reported that MCM-41 containing Cr and Ti species, prepared by a hydrolysis of TEOS, Cr(NO 3 ) 3 , and tetrabutyl titanate, promotes water splitting with higher activity than MCM-41 containing Cr alone.…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al reported that MCM-41 containing Cr and Ti species, prepared by a hydrolysis of TEOS, Cr(NO 3 ) 3 , and tetrabutyl titanate, promotes water splitting with higher activity than MCM-41 containing Cr alone. Kamegawa et al reported that MCM-41 containing Cr and Ti species, prepared by a chemical vapor deposition with TiCl 4 and CrO 2 Cl 2 , promotes photopolymerization of ethylene with higher activity than MCM-41 containing Cr alone. All these reports suggest that the incorporation of Ti to Cr-containing materials probably produces an oxo-bridged Cr–O–Ti species and shows enhanced activity, although the direct evidence for the formation of Cr–O–Ti species and the mechanism for activity enhancement are not provided.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we focused on a grafted titanium complex having a tunable coordination state. Generally, such isolated transition-metal species can be realized in porous silica networks, where they have specific tetrahedral coordination states exhibiting highly selective redox properties in the presence of oxidants and/or under photoirradiation. , In addition, because their catalytic activities are strongly dependent on the local environment around the isolated active species, their coordination design has been investigated using both bottom-up ,, and postmodification techniques. , However, as such species are presented in rigid three-dimensional (sometimes nonordered) silica networks, molecular-level design of their chemical environments is not typically possible. Furthermore, because of the formation of unusual tetrahedrally coordinated species due to the isolation of the transition metals within the silica matrix, it is difficult to obtain the respective isolated sites with high surface densities.…”
Section: Introductionmentioning
confidence: 93%